Fatal fulminant HSV-2 myocarditis: A complicated presentation - Daniele Colombo (Elsevier, 2022)
ABSTRACT: Herpes simplex virus type 2 (HSV-2) infection is the leading cause of genital lesions. Infrequently HSV-2 primary infection can spread and involve other tissue and organs, however in immunocompetent individuals extra-genital complications are rare findings. In this report we present a fatal case of fulminant myocarditis and terminal liver involvement, caused by HSV-2 infection, with a unique presentation. Diagnosis was made only post-mortem.